Case Report: Report of 2 Different Cases of Ovarian Teratoma Evaluated by Dynamic Contrast-Enhanced Ultrasound - Glutig, Katja; Alhussami, Ilmi; Krüger, Paul-Christian; Waginger, Matthias; Eckoldt, Felicitas; Mentzel, Hans-Joachim (Frontiers in Pediatrics, 2021)
Ovarian masses are not easily differentiated on transabdominal ultrasound in children. A useful supplement in various pediatric applications is dynamic contrast-enhanced ultrasound (dynCEUS). It can be performed quickly and easily. However, the literature for dynCEUS on pediatric ovarian masses is limited. We compared two cases with ovarian teratoma in which dynCEUS was a helpful additional tool.